Cross species application of quantitative neuropathology assays developed for clinical Alzheimer's disease samples. Issue 1 (1st January 2019) - Urfer, Silvan R.; Latimer, Caitlin S.; Ladiges, Warren; Keene, C. Dirk; Benbow, Sarah; Harrison, Benjamin; Promislow, Daniel E.L.; Kaeberlein, Matt; Kraemer, Brian C; Wang, Adrienne; Guscetti, Franco; Darvas, Martin
ABSTRACT: A major obstacle for preclinical testing of Alzheimer's disease (AD) therapies is the availability of translationally relevant AD models. Critical for the validation of such models is the application of the same approaches and techniques used for the neuropathological characterization of AD. Deposition of amyloid-β 42 (Aβ42) plaques and neurofibrillary tangles containing phospho-Tau (pTau) are the pathognomonic features of AD. In the neuropathologic evaluation of AD, immunohistochemistry (IHC) is the current standard method for detection of Aβ42 and pTau. Although IHC is indispensable for determining the distribution of AD pathology, it is of rather limited use for assessment of the quantity of AD pathology. We have recently developed Luminex-based assays for the quantitative assessment of Aβ42 and pTau in AD brains. These assays are based on the same antibodies that are used for the IHC-based diagnosis of AD neuropathologic change. Here we report the application and extension of such quantitative AD neuropathology assays to commonly used genetically engineered AD models and to animals that develop AD neuropathologic change as they age naturally. We believe that identifying AD models that have Aβ42 or pTau levels comparable to those observed in AD will greatly improve the ability to develop AD therapies. Abbreviations : Alzheimer's disease (AD); amyloid β 42 (Aβ42); phospho-Tau (pTau); immunohistochemistry (IHC)